2009
DOI: 10.1063/1.3236529
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the conductance of single fullerene molecules by endohedral doping

Abstract: Rights

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 31 publications
2
32
1
Order By: Relevance
“…The value obtained in this work is also rather close to the results found in the literature for pristine C 60 immobilized between gold nanoelectrodes in air (log(G/G 0 ) = -1.00) 58 and vacuum (log(G/G 0 ) = -1.00 and log(G/G 0 ) = -0.70) 29,61 but significantly higher than other reference 27 (log(G/G 0 ) = -3.60). Our value is, on the other hand, lower than the conductance of C 60 trapped between copper (log(G/G 0 ) = -0.87 to 0.18) , 54,55,59,60,[62][63][64] platinum (log(G/G 0 ) = -0.15) , 65 and silver (log(G/G 0 ) = -0.30) 61 electrodes.…”
contrasting
confidence: 58%
See 1 more Smart Citation
“…The value obtained in this work is also rather close to the results found in the literature for pristine C 60 immobilized between gold nanoelectrodes in air (log(G/G 0 ) = -1.00) 58 and vacuum (log(G/G 0 ) = -1.00 and log(G/G 0 ) = -0.70) 29,61 but significantly higher than other reference 27 (log(G/G 0 ) = -3.60). Our value is, on the other hand, lower than the conductance of C 60 trapped between copper (log(G/G 0 ) = -0.87 to 0.18) , 54,55,59,60,[62][63][64] platinum (log(G/G 0 ) = -0.15) , 65 and silver (log(G/G 0 ) = -0.30) 61 electrodes.…”
contrasting
confidence: 58%
“…27 all observed values are in the range log(G/G 0 ) = -1.0 to 0.2. 29,37,54,55,[58][59][60][61][62][63][64][65] The difference in conductance (up to factor of 20) 55 of these distinct states is, however, much lower than that one of the two well-discernible G H 1 and G L 1 features that we resolved for 1 (compare blue and red trend lines in Figure 4). We suggest therefore that different contact geometries of the C 60 anchoring groups cannot account for the existence of these two distinctly observed conductance states of molecule 1.…”
mentioning
confidence: 62%
“…In that work it is shown that the interference between pathdiffered direct and reflective ionization amplitudes induces these oscillations whose frequencies in the momentum space are directly the path differences [Eq. (9)]. The path difference between spherical direct and spherical reflected waves is always twice the radius R of the hull, simply because, no matter what direction one looks from the center, a component of the direct wave that returns travels an extra path of R ongoing + R return = 2R = D [33].…”
Section: Discussionmentioning
confidence: 99%
“…However, particularly interesting photoeffects are expected when an atom or a molecule is placed inside a fullerene, forming an endohedral compound. These nanomaterials of promising technological applications [5][6][7][8][9][10] have not only been synthesized in the laboratory [11,12], but were also found in the astrophysical environment [13]. Although a large number of theoretical studies [14][15][16][17][18][19][20][21][22][23] have been devoted to the photoresponse of the atom in endohedral captivity, there exist total photoionization cross-section measurements for only a few lanthanide endohedrals [24][25][26][27][28], * himadri@nwmissouri.edu besides a very recent experiment with the Xe@C 60 + ion [29].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these interests as well as the unique characteristics of single fullerene molecule junctions, electron transport through a single metallofullerene molecule has been investigated by several groups. [15][16][17][18][19] Senapati et al investigated the electronic structure and electron transport through a single Gd@C 82 molecule using theoretical calculations. 15 The conductance of the single Gd@C 82 molecule junction was found to be smaller than that of C 82 due to the reduction of the transmission of the conducting channels caused by the charge localization.…”
Section: Introductionmentioning
confidence: 99%